Development of analytical functions with high-performance liquid phase separation systems on the basis of the moment theory - Miyabe, Kanji (Analytical sciences, 2025)
A theoretical foundation was developed on the basis of a moment theory for investigating in detail the basic principles of separation and analysis functions of high-performance liquid chromatography (HPLC) and capillary electrophoresis (CE). Analytical capability of the “moment theory” is superior to that of conventional “plate theory” and “rate theory” in terms of accuracy, detail, and quantitativeness. Especially, only when the moment theory is applied, it becomes possible to analyze mass transfer rates and reaction kinetics in HPLC and CE systems. Various types of theoretical systems of moment analysis were constructed to achieve the multifaceted development of studies concerning HPLC and CE. Original research works relating to the following subjects were conducted on the basis of a theoretical foundation. At first, the moment theory was introduced as a superior basis for the analysis of separation behavior of HPLC and CE. Separation behavior of HPLC and CE was quantitatively analyzed in detail to accurately understand their characteristics and separation mechanisms. Then, it was theoretically considered to develop a novel separation medium and an innovative system for liquid-phase separation with extremely high efficiency. Finally, new strategies using HPLC and CE were developed for analyzing chemical phenomena, i.e., intermolecular interactions and interfacial solute permeation of spherical molecular aggregates. It was tried to demonstrate the excellent performance of HPLC and CE for the analysis of chemical phenomena to extend their applicability to new research areas other than “separation”. These research works could be conducted only using the moment theory. In this document, an overview of the original research works is provided, which were conducted on the basis of the moment theory. Graphical Abstract